Isolation and Determination of Phenolic Glycosides and Anthraquinones from Rhizomes of Various Reynoutria Species - Nawrot-Hadzik, Izabela; Granica, Sebastian; Domaradzki, Krzysztof; Pecio, Łukasz; Matkowski, Adam (Planta Medica, 2018)
Giant knotweeds of the genus Reynoutria (syn. Fallopia)–Reynoutria japonica, Reynoutria sachalinensis, and a hybrid of them, Reynoutria x bohemica–are noxious invasive plants in Europe and North America. R. japonica is a traditional East Asian (Japan and China) drug (Polygoni cuspidati rhizoma). Recently, it has been included in European Pharmacopoeia as one of the traditional Chinese medicinal herbs. In this study, a reversed-phase high performance liquid chromatography method with diode array detector and time-of-flight mass spectrometry was developed and validated for the profiling of rhizomes from European invasive populations and Polygoni cuspidati rhizoma purchased in China. Twenty-five compounds were identified, mainly stilbenes, anthraquinones, flavan-3-ols, and phenylpropanoid esters. Tatariside B, hydropiperoside, vanicoside C, a new compound (3,6-O-di-p-coumaroyl)-β-fructofuranosyl-(2 → 1)-(2′-O-acetyl-6′-O-feruloyl)-β-glucopyranoside) were reported for the first time in these raw materials. Six compounds from three phytochemical classes–stilbenes: piceid and resveratrol; anthraquinones: emodin and physcion; hydroxycinnamic sucrose esters: vanicosides A and B–were quantified using the validated method. R. japonica from China contained twice as many stilbenoids than samples from Poland (piceid 14.83 mg/g dm vs. 7.45 mg/g and resveratrol 1.29 mg/g vs. 0.65 mg/g). R. sachalinensis rhizomes contained lower quantities of anthraquinones and no detectable stilbenes, which together with higher amounts of hydroxycinnamic glycosides makes it easily distinguishable from the other two. The phytochemical profile of R. x bohemica was intermediate between the two parent species.
Keywords: LC-MS; phenolic glycosides; anthranoids; stilbenoids; flavan-3-ols; Polygonaceae; Reynoutria